Implementasi Pendekatan DMAIC untuk Perbaikan Proses Produksi Pipa PVC (Studi Kasus PT. Rusli Vinilon) - Caesaron, Dino; Simatupang, Stenly Yohanes P (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
This study focused on quality improvement on PVC production process, which has high level of product defects of 6.04%. Six sigma with DMAIC (define, measure, analyze, improve, control) approach was used to improve the process. Each step of DMAIC was conducted to carefully analyze and keep the process precisely. The PVC production process contains a number of 6722.963 product defects in million opportunities (DPMO), with sigma level of 3.97. Three priority defects, based on pareto diagram tool i.e. scorched (35.12%), failed socket (28.22%), and standard of thickness (19.24%) will be focused on. In the improve step of DMAIC, FMEA form was used to propose some recommendations in order to improve the process, that are establish a mixing process standard time, training the operator whose responsible in each PVC process, establish an oven temperature standard in socketing process, and establish a standard set up of bolt adjustment to get the appropriate thickness of pipe.